City Brand Logo Design Methodology Using Local Citizen Participation Approach - Wiratama, Danang Adi; Nugroho, Chendri Irawan Satrio (Journal of Multimedia Trend and Technology, 2024)
The cruciality of a logo for city branding interests is comparable to the need for seriousness in the design process. Several studies have stated that the main problems with city brand logo design methods are: the ineffective involvement of local communities, and the low understanding that city branding is more than just designing a logo. This study aims to formulate a city brand logo design method that (1) involves local communities and (2) is connected to the overall city branding process. To that end, a study was conducted on city branding theory, brand personality, city brand visual identity, including case studies of city brand logo design in Indonesia. The city brand logo design method formulated here is divided into the idea search stage (research, brand personality exploration, city branding concept) and the visualization stage (testing preferences for logo types and their visual elements). At each stage, community involvement is carried out through questionnaires while the design team plays a role in designing alternatives for the community. This proposed method is able to facilitate collaboration between designers and the community in designing the city's visual identity, as well as providing branding output that is (not only a logo and slogan, but) integrated with the brand's personality, core ideas, and all strategies that play a major role in implementing city branding as a whole.